Fundamentals of trigonometry - Swokowski, Earl W. (Boston, Massachusetts : Prindle, Weber & Schmidt, 1978)
The fourth edition of fundamentals of trigonometry reflects the continuing change in the needs and abilities of students who enroll in precalculus mathematics courses.
Chapter 1. Prerequisites for trigonometry -- 2. The trigonometric functions -- 3. Analytic trigonometry -- 4. Obliques triangles and vectors -- 5. Complex numbers -- 6. Exponential and logarithmic functions -- 7. Topics in analytic geometry.
Includes index.
Keywords: GEOMETRY, ANALYTIC